The role of Zionism in deposing Sultan Abdul Hamid II (1876-1909) - merah, hadi; megelatti, abdalah (Journal of Social Sciences and Humanities, 2021)
Sultan Abdul Hamid II realized that the Ottoman state - especially the emergence of its deteriorating conditions - could not survive except to rely on Muslims and Arabs and support them in the face of European interference in state affairs. His policy was to preserve the remaining states in the possession of the Ottoman Empire, and that meant that he did not provoke the wrath of Muslims and Arabs in the exercise of his political activities. And since the Zionist movement was seeking the Ottoman government to achieve the project of settling Palestine, Muslims and Arabs saw in these discussions a scientific test for the Sultan’s loyalty towards them and their sanctification. Many of them have determined their position towards Abd al-Hamid II through the laws of Jewish immigration, and through his position on the Herzl project, and from here came the Sultan's response not to agree to this project.